Listening to Community to Improve Breastfeeding Friendliness: Findings From a Community Readiness Assessment on Breastfeeding - Frieson, Tomeka; Masterson, Amelia; Tran, Victoria; Douglass, Frankie; Duffany, Kathleen (Health Promotion Practice, 2025)
Breastfeeding is a key nutritional behavior for infants during their first years of life. While prenatal breastfeeding intentions do not differ significantly between non-Hispanic Black and White mothers, the ability to meet those intentions decreases over time, and to a greater extent among Black mothers. This is partially due to environments inadequately supportive of individuals' breastfeeding needs (i.e., not breastfeeding-friendly). The Community Readiness Assessment is a powerful tool to assess a community's readiness to take action on pressing health issues. While it is frequently used to understand readiness to prevent negative health outcomes, this study explores how it can be used to understand readiness to promote breastfeeding friendliness and subsequently identify appropriate intervention strategies. Between November 2020 and June 2021, we conducted interviews with 23 key respondents in New Haven, Connecticut, representing five community sectors. Respondents scored five dimensions of readiness on a 9-point scale (1 = no awareness, 9 = community ownership). The overall community readiness score was 4.2, denoting the "preplanning" stage of readiness. The highest-scoring readiness dimension was "community knowledge about the issue" (mean score: 4.5), and the lowest-scoring dimension was "resources related to the issue" (mean score: 3.3). Small business owners reported the highest readiness score by sector (mean score: 5.0), while large employers reported the lowest (mean score: 3.1). Scores stratified by both sector and dimension revealed specific areas within the community where readiness-level-appropriate interventions could be implemented. This study highlights the benefit of assessing community readiness prior to intervention to identify tailored, equitable, and effective intervention strategies.
Keywords: Active listening; Breast feeding; Breastfeeding; Breastfeeding promotion; Community Readiness Assessment; Community health; Intervention (counseling); Psychological intervention; Scale (ratio); breastfeeding; breastfeeding-friendly; community; community assessment; community readiness; dept.hhs; public health practice